2016
DOI: 10.1155/2016/1579490
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA-ITCH Suppresses Lung Cancer Proliferation via Inhibiting the Wnt/β-Catenin Pathway

Abstract: As a special form of noncoding RNAs, circular RNAs (circRNAs) played important roles in regulating cancer progression mainly by functioning as miRNA sponge. While the function of circular RNA-ITCH (cir-ITCH) in lung cancer is still less reported, in this study, we firstly detected the expression of cir-ITCH in tumor tissues and paired adjacent noncancer tissues of 78 patients with lung cancer using a TaqMan-based quantitative real-time PCR (qRT-PCR). The results showed that the expression of cir-ITCH was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
269
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 292 publications
(275 citation statements)
references
References 55 publications
6
269
0
Order By: Relevance
“…14,15 The miR-223 is known to cause cardiac hypertrophy and the heart-related circRNA HRCR is thought to protect the heart by sponging miR-223. 49 The circRNA TTBK2 was shown to promote malignancy of gliomas by modulating miR-217 that controls hepatocyte nuclear factor 1β/Derlin-1 pathway, 50 and circRNA ITCH is known to suppress lung cancer by sponging miR-7 and miR-214 thereby suppressing the activation of Wnt/β-catenin 51 . In the present study, the circRNAs altered after stroke were identified to contain binding sites for many miRNAs indicating their potential to modulate miRNA-mediated translation and thus ischemic pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The miR-223 is known to cause cardiac hypertrophy and the heart-related circRNA HRCR is thought to protect the heart by sponging miR-223. 49 The circRNA TTBK2 was shown to promote malignancy of gliomas by modulating miR-217 that controls hepatocyte nuclear factor 1β/Derlin-1 pathway, 50 and circRNA ITCH is known to suppress lung cancer by sponging miR-7 and miR-214 thereby suppressing the activation of Wnt/β-catenin 51 . In the present study, the circRNAs altered after stroke were identified to contain binding sites for many miRNAs indicating their potential to modulate miRNA-mediated translation and thus ischemic pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in NSCLC, circ-ITCH functions as a “sponge” to block miR-7 or miR-214 and assures the stable expression of the ubiquitin E3 ligase ITCH to inhibit the Wnt/β-catenin signaling pathway, which can indirectly inhibit the proliferation of lung cancer cells through promoting the ubiquitination and degradation of Dvl2 [33]. In addition to being a microRNA “sponge” or regulator of gene transcription [34], circRNAs not only can produce pseudogenes to alter the genomic DNA composition [18, 20, 35] but also possess a protein translation function [19].…”
Section: Discussionmentioning
confidence: 99%
“…Given that circRNAs could function as miRNA sponges [33] and most of the circRNAs contain one or more miRNAs binding sites, the dysregulated circRNAs in NSCLC were likely due to an involvement in miRNA blockage, thereby contributing to the development of disease. The circRNA/miRNA interaction predicted that hsa_circRNA_404833 is potentially able to interact with miR-149-5p, which reduces cell motility and is involved in the acquired gefitinib resistance in lung adenocarcinoma [39].…”
Section: Discussionmentioning
confidence: 99%
“…These investigations have shown that circRNAs are frequently downregulated in several types of cancer (e.g., colorectal cancer, ovarian cancer, and gastric cancer) [6466]. Just few of these studies attempted to functionally explain how abnormal expression of circRNAs could impair physiological cell homeostasis and thus promote cancer phenotypes [6769]. …”
Section: Introductionmentioning
confidence: 99%